Targeted and random mutagenesis of Ehrlichia chaffeensis for the identification of genes required for in vivo infection. - Chuanmin Cheng; Arathy D S Nair; Vijaya V Indukuri; Shanzhong Gong; Roderick F Felsheim; Deborah Jaworski; Ulrike G Munderloh; Roman R Ganta (PLoS Pathogens, 2013)
Ehrlichia chaffeensis is a tick transmitted pathogen responsible for the disease human monocytic ehrlichiosis. Research to elucidate gene function in rickettsial pathogens is limited by the lack of genetic manipulation methods. Mutational analysis was performed, targeting to specific and random insertion sites within the bacterium's genome. Targeted mutagenesis at six genomic locations by homologous recombination and mobile group II intron-based methods led to the consistent identification of mutants in two genes and in one intergenic site; the mutants persisted in culture for 8 days. Three independent experiments using Himar1 transposon mutagenesis of E. chaffeensis resulted in the identification of multiple mutants; these mutants grew continuously in macrophage and tick cell lines. Nine mutations were confirmed by sequence analysis. Six insertions were located within non-coding regions and three were present in the coding regions of three transcriptionally active genes. The intragenic mutations prevented transcription of all three genes. Transposon mutants containing a pool of five different insertions were assessed for their ability to infect deer and subsequent acquisition by Amblyomma americanum ticks, the natural reservoir and vector, respectively. Three of the five mutants with insertions into non-coding regions grew well in deer. Transposition into a differentially expressed hypothetical gene, Ech_0379, and at 18 nucleotides downstream to Ech_0230 gene coding sequence resulted in the inhibition of growth in deer, which is further evidenced by their failed acquisition by ticks. Similarly, a mutation into the coding region of ECH_0660 gene inhibited the in vivo growth in deer. This is the first study evaluating targeted and random mutagenesis in E. chaffeensis, and the first to report the generation of stable mutants in this obligate intracellular bacterium. We further demonstrate that in vitro mutagenesis coupled with in vivo infection assessment is a successful strategy in identifying genomic regions required for the pathogen's in vivo growth.